MENELISIK MANFAAT EKONOMI KREATIF SEBAGAI UPAYA PENINGKATAN DAYA SAING DAERAH - Subhan Purwadinata; Tuti Handayani; M. Jumaedi; Budiman; Ali Akbar Hidayat (Juremi: Jurnal Riset Ekonomi, 2024)
The aim of this research is to gain a deeper understanding of the creative industry as a new talent that is expected to strengthen the competitiveness of the West Nusa Tenggara (NTB) region. Unemployment, poverty, and economic growth are classic issues that still require solutions. This study uses a descriptive qualitative approach with a literature review research method. The analysis results show that the creative economy is an idea that is expected to have added economic value. The creative economy is one of the alternatives to solve economic problems. However, the realization of this idea often encounters obstacles. The government and local authorities are urged to engage now in improving regulations and strengthening the creative industry. In this way, the creative industry can drive economic growth and enhance regional competitiveness.